Performance Appraisal System and Its Practices in Local Private Business Organizations of Bangladesh - Ali, Taskina (Information Management and Business Review, 2011)
This present paper focuses on the performance appraisal practices of local private organizations in Bangladesh. Here, the researchers found that, almost all the organizations have formal performance evaluation systems. Though there is variation in their methods, frequency of occurrence and parties involved in evaluation system. In terms of method majority (16%) of the organizations prefer Management by Objective (MBO) method. Concerning the frequency of performance appraisal 69.23% local organizations evaluate their employees annually. It is also observed that majority of the employees are satisfied with present performance appraisal systems. The researchers also recommend a comparative analysis between the performance appraisal practice of local private business enterprises of Bangladesh and performance appraisal practice of multinational business enterprises.